The relationship between athletes' coping strategies and indicators of dominant states - Namazov, A. K.; Olennikova, M. V.; Vasilyeva, V. S.; Grigoryev, I. A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the features of coping strategies for coping with stress among martial arts athletes with different experiences of successful competitive activities.